DAMPAK PEMBIAYAAN MURABAHAH TERHADAP LABA PT BANK BNI SYARIAH (PERSERO) TBK. KANTOR CABANG MAKASSAR - Muhlis Muhlis; Hardiyanti Ade Ahsana (Sekolah Tinggi Ekonomi dan Bisnis Syariah (STEBIS) Indo Global Mandiri, 2021)
The presence of murabahah financing service facilities at PT Bank BNI Syariah is expected to internally maximize profits for the company. For this reason, this research aims to provide empirical evidence regarding the impact of murabahah financing on profits at PT Bank BNI Syariah (Persero) Tbk. Makassar Branch Office, using 2014-2016 financial report data. The methodology uses quantitative descriptive analysis through linear regression and hypothesis testing. Research results show that murabahah financing has a positive and significant impact on profits at PT Bank BNI Syariah (Persero) Tbk. Makassar Branch Office. Hypothesis testing obtained a significant level below 5%. So that murabahah financing has a positive and significant impact on company profits. The results of the simple regression analysis showed that the model Y = -2267.044 + 0.551X. A constant value of -2267.044 means that if there is no murabahah financing, profit (Y) will decrease by -2267.044 and if the independent variable, namely murabahah financing (X) increases by one unit, the dependent variable, namely profit (Y), increases by 0.551.